POSITIONING STRATEGIES IN TIMES OF COVID-19 OF THE COMPANY D. FRUTITOS E.I.R.L - SAN JUAN DE LURIGANCHO, 2020 - Seminario-Unzueta, Randall (2020)
Objectives: To determine the positioning strategies in times of COVID-19 of the company D. Frutitos E.I.R.L - San Juan de Lurigancho, 2020. Materials and methods: The study of the research is descriptive of qualitative approach, with non-experimental design, according to the data collected, it will be designed an applied research, counting as a population the clients of the company D. Frutitos EIRL, with a total sample of 80 consumers between men and women over 18 and under 60 years old, the data collection instrument was the questionnaire and They will be analyzed through the Statistical Package for the Social Sciences (SPSS) program. Results: It was determined that the positioning strategies are positively occurring at a high level with 65.0%, regarding consumer management, it was determined that it is being applied correctly with a high level of 68.8%, regarding Marketing A high level assessment is reached with 70.0%, regarding Brand Management it is applied at a high level of 68.8% and with respect to the competition it was observed that a low level of 42.5% does not identify the competitors. Conclusions: Regarding the present research work, it concludes with the identification of the positioning strategies in times of COVID-19 of the company D. Frutitos EIRL, it was shown that the strategies are being executed at a high level, then in the dimensions, high, medium and high levels were obtained low.